Association of Type 2 Diabetes Risk with Some Anthropometric Measurements in Obese Adults - Bardak Perçinci, Nazal (Progress in Nutrition, 2022)
Type 2 diabetes can be defined as an insidious disease that can last for years without symptoms. Disease In type 2 diabetes, insulin resistance and insulin secretion deformation are predominant and account for about 90-95% of all diabetics (5). The major disadvantage of delayed diagnosis is the increased risk of complications. The management of risk factors and risk factors that can be considered as a finding can prevent the disease or keep it uncomplicated (6). A total of 95 obese women adults with a mean age of 33.65 ± 1.62 years were included in this study. All cases were women. The Finnish Type-2 DM Risk Scale (FINRISK) was used to determine the risk of type 2 diabetes. FINDRISK (diabetes risks) scoring results of the participants are given in Table 2. According to this distribution, 15.8% of the participants were low risk, 26.3% were mild risk, 28.4% were medium risk, 13.7% were high risk and 15.8% were carries a very high risk. When body weight and risk scoring were evaluated, body weight was found to be statistically significant between the low-risk group and the high-risk group and the low-risk group and the medium-risk groups (<0.001). The difference between BMI values ​​between low risk group and medium risk group, low risk group and mild risk group and between high risk and very high risk groups were found to be statistically significant (<0.001). No statistical significance was found between height and body fat percentage (%) values. The difference between waist circumference, hip circumference and waist / hip ratio values ​​between low risk group and medium risk group, between low risk group and high risk group, and between mild risk and high risk groups were statistically significant (<0.001).